Teacher returnees from overseas programs in the west: a narrative study in Vietnam - Vu, Ngoc Tung; Ta, Thi Mai Huong; Le, Thi Thu Huong (Frontiers in Communication, 2024)
In this research study that employs a narrative inquiry approach, we were interested in examining teacher identity as a subject of attention in tandem with the growing research on language teacher education and teacher professional development. By drawing on the theories of teacher identities, as laid out by Bourdieu (1986) and Bennett (1986, 1997), it was possible to conclude that the teacher identities of this study's participants both continually changed and dynamically evolved. Particularly, their teacher identity appeared to form as a result of their engagement in overseas educational programs. Participants returned with hope that they could maintain their newly transformed perspectives on teaching and learning. The teacher returnees were returnees were observed during conversations, and their reflections over time were analyzed and interpreted. These conversations and stories were often shared in social settings, and the relevant teaching practices that were learned overseas, or their fields, as defined by Bourdieu (1986), formed a large basis of their reflections. To conclude, further research and implications were discussed to support the continuation of this important topic.